Delayed enhancement of the intraventricular septum following an extraordinary endurance exercise. (2nd December 2010) - Bhella, Paul S; Kelly, Jacob P; Peshock, Ronald; Levine, Benjamin D
Abstract : Cardiac fatigue and elevations in cardiac biomarkers have been described following prolonged exertion in endurance athletes. We comprehensively evaluated a highly trained 46-year-old man attempting a North American transcontinental run in a record time of 45 consecutive days. After running 1460 km and ascending over 2600 m, the run was ended prematurely on day 17 following a leg injury; in support of the event, the subject cycled an additional 1580 km. Echocardiography and biomarker analysis performed pre-event and while running revealed no decrement in systolic function and undetectable levels of troponin I and T. Post-event cardiac MRI demonstrated the interval appearance of delayed enhancement of gadolinium at the inferior insertion of the right ventricle and in the interventricular septum—a novel finding that may represent subtle inflammation secondary to a combined exercise and altitude effect.